The transactivating domain of the c-Jun proto-oncoprotein is required for cotransformation of rat embryo cells. - Alani, R (1991)
The nuclear phosphoprotein c-Jun, encoded by the proto-oncogene c-jun, is a major component of the AP-1 complex. A potent transcriptional regulator, c-jun is also able to transform normal rat embryo cells in cooperation with an activated c-Ha-ras gene. By deletion analysis, we identified the regions of c-Jun encoding transformation and transactivation functions. Our studies indicate that there is a direct correlation between the ability of the c-Jun protein to activate transcription and cotransform rat embryo cells. The regions involved in these functions include the conserved leucine zipper/DNA binding domain and an effector domain near its N terminus. This N-terminal region spans amino acids 61 to 146 of the c-Jun protein and is highly conserved among all Jun family members. These results support the hypothesis that c-Jun transforms cells by stimulating the expression of transformation-mediating genes.